The Clinical Study on Acupuncture Sensation in CC, CF and BV Herbal Acupuncture -The Basic Study on Placebo Herbal Acupuncture - Seo Jung-Chul; Yoon Jong-Seok; Han Sang-Won; Park Hi-Joon; Lee Hye-Jung (Journal of pharmacopuncture, 2004)
Objective : This study was designed to find out whether NS(normal saline) is able to be constituted as an appropriate control group for CC(Cervi Cornu Parvum herbal acupuncture), CF(Carthami-Flos herbal acupuncture) and BV(bee venom herbal acupuncture). Methods : NS and three herbal acupuncture were inserted into Quchi(LI 11) of the subjects. After 5 minutes the subjects completed a questionnaire rating the intensity of 21 kinds of acupuncture sensation; hurting, penetrating, sharp, aching, intense, spreading, radiating, tingling, pricking, stinging, pulling, heavy, dull, numb, electric, shocking, hot, burning, cool, pulsing, and throbbing. We compared subjective evaluations of acupuncture sensation between or among the groups. Results : As for CC half items of the acupuncture sensation were significantly different from NS. As for CF all items were not significantly different from NS. As for CC all items were significantly different from NS except one item. In general the score of CF acupuncture sensation was lower than the others and the score of BV acupuncture sensation was higher than the others from comparison of sensation among herbal acupunctures(CC, CF, BV). Conclusion : We found that NS is able to be an appropriate placebo herbal acupuncture for CF. Further study is needed for new placebo herbal acupuncture for CC and BV.